Optical Characterization of Carbon Quantum Dots Under Laser, Magnetic and Heat Treatment - Kamat, Raman K.; Hangsarumba, Surendra; Das, Santosh K.; Gupta, Suresh P.; Shrestha, Prakash M.; Yadav, Kishori; Dhobi, Saddam H. (Journal of Nepal Physical Society, 2025)
Carbon quantum dots (CQDs) are emerging nanomaterials with unique optical properties that can be tuned by concentration and external conditions. However, their nonlinear behavior under laser, magnetic, and thermal treatments remains insufficiently explored. Understanding how these factors influence refractive index and transmittance is crucial for advancing their application in optoelectronic devices, sensors, bio-imaging, and energy systems. This work aimed to synthesize and characterize the optical properties of CQDs solution at different concentrations (100%, 50%, 25%, 12.5% by volume) under various environmental conditions, including laser exposure, magnetic field, and heat. CQDs were prepared by mixing citric acid (C6 H8 O7 ) and thiourea (CH4 N2 S) in a 2:1 weight ratio (1 g: 0.5 g) and heating in a microwave oven (1100 W) at 200–250 oC until the mixture formed a dark brown solid. The solid was dissolved in 40 mL distilled water with magnetic stirring for 1 hour and filtered to obtain the 100% concentration solution, which was then diluted to prepare 50%, 25%, and 12.5% solutions. Optical studies were performed using a rotating spectrometer and Theremino spectrometer under the specified environmental conditions. Results showed that the refractive index exhibited nonlinear behavior under laser treatment across all concentrations and was further influenced by magnetic fields, initially increasing to a maximum before decreasing, while at 100% concentration it continuously declined. Temperature also induced nonlinear changes in refractive index, particularly at higher concentrations. Transmittance varied with wavelength (400–700 nm) and treatment: under laser exposure, 100% concentration first decreased then increased, whereas lower concentrations increased steadily. Under magnetic fields, transmittance decreased continuously for 100% and 50% concentrations, but for 25% and 12.5%, it reached a minimum before rising. Temperature similarly affected transmittance, with higher concentrations showing a continuous decrease, 25% showing a minimum before increasing, and 12.5% increasing steadily. These findings highlight the complex interplay of concentration, environmental factors, and wavelength on the optical behavior of CQDs solution.